2019
DOI: 10.3390/nano9121680
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propulsion Strategies for Artificial Cell-Like Compartments

Abstract: Reconstitution of life-like properties in artificial cells is a current research frontier in synthetic biology. Mimicking metabolism, growth, and sensing are active areas of investigation; however, achieving motility and directional taxis are also challenging in the context of artificial cells. To tackle this problem, recent progress has been made that leverages the tools of active matter physics in synthetic biology. This review surveys the most significant achievements in designing motile cell-like compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…Only a handful of studies have been reported using liposomes to achieve directional/active motion, 20 however. Taking a biohybrid approach, Kurakazu and co-workers attached flagella of Chlamydomonas, a biflagellate unicellular alga, to microsized liposomes, which display enhanced diffusion in the presence of ATP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Only a handful of studies have been reported using liposomes to achieve directional/active motion, 20 however. Taking a biohybrid approach, Kurakazu and co-workers attached flagella of Chlamydomonas, a biflagellate unicellular alga, to microsized liposomes, which display enhanced diffusion in the presence of ATP.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Afterwards, we simulated with the neighboring parameter values to investigate how PFKL condensates formation was affected by. Second, to estimate a friction coefficient, we surveyed a range of propulsion velocity of various biomolecules as in the order of 10~10 3 𝜇𝜇𝑚𝑚𝑠𝑠𝑠𝑠𝑠𝑠 −1 (Feng and Gilson, 2019;Jee et al, 2018;Santiago and Simmel, 2019). At the same time, some enzymes appear to show moderate to least amount of self-propulsion so that they were observed to move with a speed in a range of 0.1~2.5 𝜇𝜇𝑚𝑚𝑠𝑠𝑠𝑠𝑠𝑠 −1 (Arque et al, 2019).…”
Section: Parameter Estimation Of the Modelmentioning
confidence: 99%
“…Self-propelled micro/nanomotors are molecular machines that convert external energy to mechanical motion. The motors have attracted attention for constructing artificial micro/nanorobots for various applications such as biomedicines, sensing, and molecular robotics. Various external stimuli have been used for motor propulsion, including chemical reactions, , magnetic fields, ,, electric fields, , ultrasound, ,, and light. Light is an attractive energy source because of the facile manipulation of ON/OFF switching, energy input, and direction. In nature, several micro-organisms can be known as phototaxis, a form of locomotory movement based on sensing the direction of light and either swimming toward (positive phototaxis) or away (negative phototaxis) from the light source . For instance, Chlamydomonas is a unicellular photosynthetic alga that shows both positive and negative phototaxis using a complex light detection system .…”
Section: Introductionmentioning
confidence: 99%